Proceedings of 2nd Annual Management, Business and Economic Conference (AMBEC 2020) 2021
DOI: 10.2991/aebmr.k.210717.022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Due Professional Care, Integrity, Confidentiality, and Independence on Audit Quality

Abstract: This study aimed to analyze the effect of due professional care, integrity, confidentiality, and independence on audit quality. Moreover, define the most required topic of advanced professional training related to increase the professionalism of auditor which was appropriate in this pandemic. The object of the research were public accountant firms in East Java, Indonesia. The data were collected through questionnaires which was conducted during the pandemic. Based on the sample collection using purposive sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Auditor's honesty, diligence, responsibility, and objectivity enhance the integrity and must be maintained to achieve audit quality. The results confirm the second hypothesis that integrity has a positive influence on audit quality are in line with research conducted by Octaviani & Ekasari (2021); Prabowo & Suhartini (2021); Kamil & Fathonah (2020); Kertarajasa et al (2019); Hikmayah & Aswar (2019); Wardayati (2016); Bouhawia et al (2015); and Furiady & Kurnia (2015).…”
Section: 119supporting
confidence: 91%
See 1 more Smart Citation
“…Auditor's honesty, diligence, responsibility, and objectivity enhance the integrity and must be maintained to achieve audit quality. The results confirm the second hypothesis that integrity has a positive influence on audit quality are in line with research conducted by Octaviani & Ekasari (2021); Prabowo & Suhartini (2021); Kamil & Fathonah (2020); Kertarajasa et al (2019); Hikmayah & Aswar (2019); Wardayati (2016); Bouhawia et al (2015); and Furiady & Kurnia (2015).…”
Section: 119supporting
confidence: 91%
“…Researchers have shown that auditor integrity is a critical factor in the audit process and positively affects audit quality (Octaviani & Ekasari, 2021;Prabowo & Suhartini, 2021;Kamil & Fathonah, 2020;Kertarajasa et al, 2019;Hikmayah & Aswar, 2019;Wardayati, 2016;Bouhawia et al, 2015;Furiady & Kurnia, 2015).…”
Section: Impact Of Integrity On Audit Qualitymentioning
confidence: 99%
“…402667 which is more than 1.96. This research is not in line with previous research conducted by Octaviani et al (2021) which has no significant influence on audit quality.…”
Section: Discussioncontrasting
confidence: 99%
“…This study is additionally backed by Octaviani et al (2021), who examined the impact of due professional care on the quality of audits. The test findings indicate a discernible impact on the quality of audits.…”
Section: The Effect Of Due Professional Care On the Quality Of Audit ...mentioning
confidence: 99%
“…However, independence becomes a concern when the former auditor accepts the position after issuing a positive judgment on the accounts. Nonetheless, these results are not confirmed by the study of Geiger et al (2005) having given proof of no relationship between the perceived independence and the company hiring a former auditor (Khasharmeh and Desoky, 2018;Barghathi et al, 2020;Octaviani and Ekasari, 2021).As a consequence, we postulate the following hypothesis:…”
Section: 23mentioning
confidence: 64%